Income and Terrorism: Insights from Subnational Data - Michael Jetter; Rafat Mahmood; David Stadelmann (Institute of Labor Economics (IZA), 2021)
To better understand potential relationships between income and terrorism, we study data for 1,527 subnational regions in 75 countries between 1970 and 2014. Results consistently imply an inverted U-shape that remains robust to accounting for a comprehensive set of region-level covariates, region- and time-fixed effects, as well as estimating an array of alternative specifications. The threat of terrorism systematically rises as low-income polities become richer, peaking at an income level of about US12,800 per capita (in constant 2005 PPP US), but then falls consistently above that level. This pattern emerges for domestic and transnational terrorism alike. Peaks in the income-terrorism relationship differ by perpetrator ideology. Thus, alleviating poverty per se may first exacerbate terrorism, contrary to much of the proposed recipes advocated since 9/11.
Keywords: D74; O11; 330; subnational income; subnational terrorism; domestic terrorism; transnational terrorism; terror group ideology